HUBUNGAN PENERAPAN 5 PILAR SANITASI TOTAL BERBASIS MASYARAKAT (STBM) DAN KEJADIAN DIARE DI DESA TAMAN BARU KECAMATAN PENENGAHAN KABUPATEN LAMPUNG SELATAN - Monica, Deta Zalva; Ahyanti, Mei; Prianto, Nawan (Poltekkes Kemenkes Tanjung Karang, 2020)
Diarrhea affects the death of several people around the world. In Lampung Province, the morbidity rate for all age groups tended to increase in 2005-2014. The increase in cases also occurred in South Lampung Regency from 2016-2018, and the most in Taman Baru Village, Penengah District.The study used a cross-sectional design with a sample of 267 households, which are all households in Taman Baru Village. Primary data were collected through a survey using a questionnaire and checklist. The collected data were processed and analyzed in a bivariate manner with the help of a computer program.The results showed a relationship between knowledge and application of the five pillars of STBM and the incidence of diarrhea. Community leaders and village officials fully support STBM activities. The people of Taman Baru Village have not carried out liquid waste management and household waste management, this factor can be the cause of the increasing incidence of diarrhea.